Strategi Manajemen Pendidikan Islam dalam Meningkatkan Mutu Hafalan Santri di Ma’had Tahfiz Vokasional - Muhammad Syifaa’ul Qolbi; Ita Nurmalasari; Adi Wibowo (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
This study examines the strategy of Islamic education management in improving the quality of students' Quran memorization at Ma'had Tahfiz Vokasional. The research focuses on analyzing the implementation of an integrated education model that combines Quran memorization with vocational education. Using a qualitative case study design, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that improvements in students' memorization quality are achieved through an integrated curriculum management strategy with balanced proportions of tahfiz, vocational training, and character development. This strategy is strengthened by professional human resource management through selective recruitment and continuous capacity building for tahfiz instructors. The learning process is systematically managed by integrating classical and modern methods within a comprehensive, tiered system. A conducive learning environment is created through the implementation of Arabic language immersion (bi'ah lughowiyah) and the utilization of educational technology. A continuous evaluation system and a strategic partnership with parents support the entire process. The research findings indicate that integrating vocational education enhances memorization quality through intellectual refreshment mechanisms and by building students' self-confidence. This management model offers a new paradigm in tahfiz education that successfully balances spiritual excellence with contemporary social relevance.